OPTIMALISASI REFORMA AGRARIA MELALUI PEMBENTUKAN PENGADILAN KHUSUS PERTANAHAN - Rindu Audrye Salma Rizqila (Magister Hukum Universitas Semrang, 2024)
This research aims to understand how essential the establishment of a special land court is in the current era in order to facilitate government policies regarding agrarian reform by looking at current cases, country comparisons, how the special court is structured, and the formulation of its judges. Soil is one type of earth's wealth that is fundamental for life. In implementing the agrarian reform policy, it is basically targeting land legalization of assets that are the object of ownership disputes between the community, companies, and government agencies, as well as land owned by the community that has not received legal certainty as the owner of the land rights of the agrarian reform object (TORA). However, in reality, regulating land ownership is not easy, so land disputes often arise that take time to resolve and ultimately hamper policies, one of which is regarding agrarian reform. This is the urgency of the need to establish a special land court. The method used in this research is normative juridical, with statutory, case, and conceptual approaches. The results of this research are that the formation of this court will be under the Supreme Court court chambers, in this case the general court, with a composition of three judges consisting of one career judge and two ad hoc judges, which of course cannot be separated from land certification, the basis of which will be regulated in law.